2023
DOI: 10.1111/1744-7917.13268
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to sublethal concentration of flupyradifurone alters sexual behavior and cuticular hydrocarbon profile in Heriades truncorum, an oligolectic solitary bee

Samuel Boff,
Manfred Ayasse

Abstract: The aboveground oligolectic bee, Heriades truncorum, is a particularly good model for studying the impact of pesticides on sexual communication, since some aspects of its mating behavior have previously been described. We have tested (1) the interference of the pesticide flupyradifurone on male precopulatory behavior and male mating partner preferences, (2) the way that the pesticide interferes in male quality assessment by the female, and (3) the effects of the pesticide on the chemical compounds in the femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…Consistent with these considerations, treating males, females, or both partners with insecticides reduced the mating frequency in our experiments to levels as low as 35% for flupyradifurone. A recent study demonstrated that sublethal doses of flupyradifurone modified the cuticular hydrocarbon profile in an oligolectic bee (Boff & Ayasse, 2023). In our study, treatment of females with flupyradifurone reduced the mating frequency at any of the tested doses.…”
Section: Discussionsupporting
confidence: 53%
“…Consistent with these considerations, treating males, females, or both partners with insecticides reduced the mating frequency in our experiments to levels as low as 35% for flupyradifurone. A recent study demonstrated that sublethal doses of flupyradifurone modified the cuticular hydrocarbon profile in an oligolectic bee (Boff & Ayasse, 2023). In our study, treatment of females with flupyradifurone reduced the mating frequency at any of the tested doses.…”
Section: Discussionsupporting
confidence: 53%
“…Pesticides can also alter bee olfactory processing (Mustard et al, 2020;, as well as cuticular hydrocarbons (Boff & Ayasse, 2023), meaning that communication around the formation of dominance hierarchies may be disrupted by pesticide exposure. Indeed, previous work has found that bumblebee (B. impatiens) colony-level social networks become smaller with workers interacting less with each other when they are exposed to the neonicotinoid imidacloprid (Crall et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…FPF can also impair reproductive output in solitary bee species (Osmia bicornis and Xenoglossa pruinosa) (Knauer et al, 2022;Rondeau & Raine, 2024) and can impact mating behaviour in another solitary bee (Heriades truncorum) (Boff & Ayasse, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Less is known about the impact of flupyradifurone on non- Apis bees, but acute exposure to the pesticide can impair bumblebee ( B. impatiens ) learning and memory [ 38 ], and chronic exposure can harm bumblebee ( Bombus terrestris ) colony growth [ 56 ]. Exposure to Sivanto, a chemical formulation containing flupyradifurone, can also have both lethal and sub-lethal impacts on solitary bees [ 14 , 57 , 58 ].…”
Section: Introductionmentioning
confidence: 99%